The Cytotoxic Activities of the Extracts of Sengkubak (Pycnarrhena cauliflora) As Apoptosis Inducers to Hela Cervical Cancer Cells - Masriani (Journal of Chemical Natural Resources, 2019)
Cancer has been considered as problematic medical issues both in developed and developing countries. Pycnarrhena cauliflora or Sengkubak (Pycnarrhena cauliflora) has a potential value as alternatives for anticancer medication. This study aims to evaluate the cytotoxic activities of Sengkubak (Pycnarrhena cauliflora), and investigate the induction for apoptosis mechanisms from the extracts n-hexane, dichloromethane, and methanol from roots, branches the leaves to HeLa cancer cells. The cytotoxic activities were analyzed by performing MTT methods, while induction analysis of apoptosis was conducted by utilizing the Acridine Orange/Ethidium Bromide (AO/EB) as visual nuclear methodologies. The extracts of roots dichloromethane showed the highest cytotoxic activities accounted for IC50 70Âµg/mL and these extracts were able to induce the apoptosis mechanisms. This study concludes that the Sengkubak (Pycnarrhena cauliflora) has the ability as a potential alternative for anticancer medications.